Research Progress of Traditional Chinese Medicine in Treatment of Myocardial fibrosis - Ren, Chunzhen; Liu, Kai; Zhao, Xinke; Guo, Huan; Luo, Yali; Chang, Juan; Gao, Xiang; Lv, Xinfang; Zhi, Xiaodong; Wu, Xue; Jiang, Hugang; Chen, Qilin; et al. (Frontiers in Pharmacology, 2022)
Effective drugs for the treatment of myocardial fibrosis (MF) are lacking. Traditional Chinese medicine (TCM) has garnered increasing attention in recent years for the prevention and treatment of myocardial fibrosis. This Article describes the pathogenesis of myocardial fibrosis from the modern medicine, along with the research progress. Reports suggest that Chinese medicine may play a role in ameliorating myocardial fibrosis through different regulatory mechanisms such as reduction of inflammatory reaction and oxidative stress, inhibition of cardiac fibroblast activation, reduction in extracellular matrix, renin-angiotensin-aldosterone system regulation, transforming growth Factor-β1 (TGF-β1) expression downregulation, TGF-β1/Smad signalling pathway regulation, and microRNA expression regulation. Therefore, traditional Chinese medicine serves as a valuable source of candidate drugs for exploration of the mechanism of occurrence and development, along with clinical prevention and treatment of MF.